2016
DOI: 10.1007/s10661-016-5462-5
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of acid mine drainage generation potential of various lithologies using static tests: Etili coal mine (NW Turkey) as a case study

Abstract: The Etili neighborhood in Can County (northwestern Turkey) has large reserves of coal and has been the site of many small-to medium-scale mining operations since the 1980s. Some of these have ceased working while others continue to operate. Once activities cease, the mining facilities and fields are usually abandoned without rehabilitation. The most significant environmental problem is acid mine drainage (AMD). This study was carried out to determine the acid generation potential of various lithological units … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 33 publications
0
13
0
1
Order By: Relevance
“…In addition, the sulfur content was in the range between 2.51 and 13.1 wt% S. Table 3 shows the results obtained from the NAG test performed. NAG pH has been proposed as single indicator (or in combination with other static tests) of the potential of the samples to generate acidity; samples with NAG pH below 4.5 are potentially acid forming (PAF) [38][39][40]. This parameter is generally more appropriate since it is the result of the balance between the ability to produce acid and the neutralizing capacity of the rocks, while other parameters calculate the potential to generate acid from the sulfur content by overestimating that capacity since there are sulfur-containing minerals (including many sulfides) that are not acid-producing minerals.…”
Section: Zn (G•lmentioning
confidence: 99%
“…In addition, the sulfur content was in the range between 2.51 and 13.1 wt% S. Table 3 shows the results obtained from the NAG test performed. NAG pH has been proposed as single indicator (or in combination with other static tests) of the potential of the samples to generate acidity; samples with NAG pH below 4.5 are potentially acid forming (PAF) [38][39][40]. This parameter is generally more appropriate since it is the result of the balance between the ability to produce acid and the neutralizing capacity of the rocks, while other parameters calculate the potential to generate acid from the sulfur content by overestimating that capacity since there are sulfur-containing minerals (including many sulfides) that are not acid-producing minerals.…”
Section: Zn (G•lmentioning
confidence: 99%
“…Figure 3a,b presents the particle size distribution and moisture retention curves, respectively, for the till material used in the cover and the waste rock material. Acid base accounting (ABA) tests are well established and widely accepted to characterize waste rock acidity [35,36]. ABA tests were performed on eight waste rock samples that were collected during drilling of the four CMT wells: One shallow and one deep sample were used from each CMT well.…”
Section: Materials Characterizationmentioning
confidence: 99%
“…The key remedial objective at the Lingan WRP was to attenuate the impact of AMD to the primary environmental receptors (groundwater and Graces Brook) over time. Acid base accounting (ABA) tests are well established and widely accepted to characterize waste rock acidity [35,36]. ABA tests were performed on eight waste rock samples that were collected during drilling of the four CMT wells: One shallow and one deep sample were used from each CMT well.…”
Section: Site Remediation and Monitoringmentioning
confidence: 99%
“…The MTs samples used in this study were collected in acidic zones of the TSF which was confirmed by the paste pH (3.1) of the MTs, revealing the elevated acidity of the MTs. Low paste pH can be related to iron sulfide oxidation and also to soluble mineral dissolution [32]. The modified ABA test classified the MTs sample as having low sulphide-S content (6.1%) and highly negative values of NNP (-210 kg CaCO 3 /t) indication that the MTs are likely to generate ARD when exposed to atmospheric conditions [33].…”
Section: B Static Tests Predictionsmentioning
confidence: 99%